Planning for success: Why conservation programs need a strategic program for recovering species. Issue 9 (13th August 2019) - Adams, Vanessa M.; O'Donnell, Jessica; Burley, Alana; Lawson, James; Auld, Tony D.; Brazill‐Boast, James; Laws, Claire A.; Gallagher, Rachael V.
Abstract: A substantial amount of money has been spent globally on threatened species management. While the number of threatened species continues to increase, we would expect to observe a portion of those receiving active management to respond positively and recover over time. Management of these recovering species requires a different approach to those which are declining. In particular, recovering species may require active monitoring as the primary management activity, once the threats causing their initial decline have been managed such that populations are stable or increasing. When prioritizing funding actions to improve species persistence (in particular with species prioritization approaches such as cost‐effectiveness rankings), we demonstrate that monitoring species to track their continued improvement would only occur in the (unlikely) scenario of comprehensive program funding. We provide one easily implemented solution to this—the establishment of a separately funded transitional management stream within which recovering or recovered species are prioritized for monitoring from a dedicated monitoring budget. We present a set of criteria to assess recovering species eligible for this management arrangement and demonstrate the successful application of this approach in New South Wales, Australia in the Saving our Species program.